2018
DOI: 10.1021/acs.jpclett.8b03582
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Anisotropic Molecular Packing in Vapor-Deposited Alq3 Glasses

Abstract: Anisotropic molecular packing is a key feature that makes glasses prepared by physical vapor deposition (PVD) unique materials, warranting a mechanistic understanding of how a PVD glass attains its structure. To this end, we use X-ray scattering and ellipsometry to characterize the structure of PVD glasses of tris(8-hydroxyquinoline) aluminum ( Alq3), a molecule used in organic electronics, and compare our results to simulations of its supercooled liquid. X-ray scattering reveals a tendency for molecular layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 53 publications
8
72
0
Order By: Relevance
“…The anisotropy has often been observed in the amorphous films of vacuum‐deposited organic semiconductors 1,2,19 . Ediger et al reported a surface equilibrium mechanism, which shows that anisotropy is inherited from the surface structure 14,19 . When the molecules arrive at the film surface during the vacuum deposition, they can move to find their stable positions even below the glass transition temperature because mobility at the surface could be much higher than that in the bulk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anisotropy has often been observed in the amorphous films of vacuum‐deposited organic semiconductors 1,2,19 . Ediger et al reported a surface equilibrium mechanism, which shows that anisotropy is inherited from the surface structure 14,19 . When the molecules arrive at the film surface during the vacuum deposition, they can move to find their stable positions even below the glass transition temperature because mobility at the surface could be much higher than that in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, anisotropic amorphous films are formed. This surface equilibration mechanism has been recently applied to explain the formation mechanism of SOP in Alq 3 film 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[110,[117][118][119] More research efforts are required to develop faster and more universal methodologies so that molecular simulations may become an important tool for the experimentalists, in silico screening the OLED emitter-host pairs for optimizing the light outcoupling efficiencies. As pointed out by Bagchi et al, [129] the demonstrated correlation between the molecular orientations in vacuum-deposited films and at the surface of a supercooled liquid may open up a possible route towards a far less computationally expensive algorithm. We envision that more research efforts in this field would shorten the development of new OLED molecules.…”
Section: Part 3: Computer Simulationsmentioning
confidence: 91%
“…Even molecules with a nearly spherical shape can form anisotropic glasses, exhibiting a tendency toward molecular layering and polar alignment of the molecular dipoles. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%